Caminhos de Ferro e Turismo em Portugal (final do século XIX e primeiras décadas do século XX) - Ribeiro, Elói (2009)
As the construction of railway lines required high levels of capital investment, one of the concerns of the Railways Companies was to obtain the economies of scale which would allow a return on the capital invested. For this reason, more intense utilization and diversification of the system became necessary and, therefore, since the end of the 19th century the companies developing and exploiting of the railways put into practice a series of commercial strategies which sought to attract new consumers, particularly those travelling for pleasure or for summer vacations, as it was the case of the tourists. With this objective in mind, the Railways Companies published travel guides, put into effect special tariffs, particularly during the months of ‘sea bathing’, and organized trips at the times of special events such as exhibitions, congresses and fairs, or to destinations whose beauty or whose monuments would attract tourists. So in Portugal as happened in other European countries, the guides emerged linked to the development of the railways. To promote the development of group’s travels since de last decades of the 19th century reduced tariffs were applied to excursion groups, or college and teacher groups. The practice of reducing prices was equally applied during the months of ‘sea bathing’ and during the time when there were major exhibitions in Portugal or abroad and even special trips to these events were organized. As an incentive to encourage travel, from the 1880s emerged the idea of round trips in Portugal and abroad, particularly in Spain and France. This second model of travel resulted from a combined service between the Portuguese companies and various Spanish and French companies. Also with the objective to encourage the tourist’s travels in 1906, the railway companies proposed a new type of ticket – ‘kilometre tickets’ – through which the customer paid for the kilometers travelled, independently of the destination of the journey. In this paper we intended to analyze same of the initiatives of the Portuguese railways companies to encourage the utilisation of railways, namely by promoting the tourism.